Serotonin 1A receptor agonist increases species- and region-selective adult CNS proliferation, but not through CNTF - Arnold, Sheila A. (2012)
Endogenous ciliary neurotrophic factor (CNTF) regulates neurogenesis of the adult brain in the hippocampal subgranular zone (SGZ) and the subventricular zone (SVZ). We have previously shown that the cAMP-inhibiting D2 dopamine receptor increases neurogenesis by inducing astroglial CNTF expression. Here, we investigated the potential role of CNTF in the proliferative response to pharmacological stimulation of the serotonin 1A (5-HT1A) receptor, which also inhibits cAMP, in adult mice and rats. Like others, we show that systemic treatment with the active R-enantiomer of the 5-HT1A agonist 8-Hydroxy-2-(di-n-propylamino)tetralin (8-OH-DPAT) induces proliferation in the SGZ in rats using unbiased stereology of 5-Bromo-2′-deoxyuridine (BrdU) positive nuclei. However, despite the bioactivity of R-8-OH-DPAT, as also shown by a decrease in hippocampal nNOS mRNA levels, it did not increase CNTF mRNA as shown by highly specific quantitative RT-PCR (qPCR). Surprisingly, R-8-OH-DPAT did not cause an increase in SVZ proliferation in rats or in either the SVZ or SGZ of two different strains of mice, C57BL/6J, and 129SvEv, using acute or chronic treatments. There also were no changes in CNTF mRNA, and also not in mice treated with a widely used racemic mixture of 8-OH-DPAT, higher doses or after intracerebral injection, which reduced nNOS. In contrast to the others, we propose that the 5-HT1A receptor might be non-functional in mice with regards to regulating normal neurogenesis and has region-selective activities in rats. These species- and region-specific actions raise important questions about the role of the 5-HT1A receptor in human neurogenesis and its implications for the field of depression.